Cytokinin production by Pseudomonas fluorescens G20- 18 determines biocontrol activity against Pseudomonas syringae in Arabidopsis - Grobkinsky, Dominik K. (2016)
Fil: García de Salamone, Inés Eugenia. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Biología Aplicada y Alimentos. Cátedra de Microbiología Agrícola. Buenos Aires, Argentina.